2016
DOI: 10.1111/jcpt.12388
|View full text |Cite
|
Sign up to set email alerts
|

Update meta-analysis of theCYP2E1 RsaI/PstI andDraI polymorphisms and risk of antituberculosis drug-induced hepatotoxicity: evidence from 26 studies

Abstract: This meta-analysis suggests that there is an increased risk of ATDH in individuals carrying the C1/C1 genotype of the CYP2E1 RsaI/PstI polymorphism. However, no association was found for the DraI polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…The studies included in the meta-analysis examined Chinese, Korean, and Japanese populations. Recently, an updated meta-analysis assessed a larger set of data from 26 studies with a total of 7423 participants [58]. The results confirmed an increased risk of the CYP2E1 C1/C1 genotype for occurrence of AT-DILI.…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 84%
“…The studies included in the meta-analysis examined Chinese, Korean, and Japanese populations. Recently, an updated meta-analysis assessed a larger set of data from 26 studies with a total of 7423 participants [58]. The results confirmed an increased risk of the CYP2E1 C1/C1 genotype for occurrence of AT-DILI.…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 84%
“…In CYP2E1 , two polymorphisms are most commonly studied ( RsaI/PstI (rs2031920/rs3813867) and DraI (rs6413432)). rs2031920 and rs3813867 are in complete linkage disequilibrium in East Asians [ 16 ]. A recent meta-analysis found that the RsaI/PstI polymorphism c1/c1 (major allele for both SNPs) confers a higher risk of INH-DILI with an OR of 1.32 compared to the c1/c2 or c2/c2 genotypes, but no increase in risk for the DraI polymorphism [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphic variants, existing in the functional genes of the cytochrome P450 system, are associated with the pathogenesis of several clinical cancers [ 2 , 3 ]. For example, rs2031920 C/T with an Rsa I restriction enzyme site and rs3813867 C/T with a Pst I restriction enzyme site are two common single nucleotide polymorphisms (SNP) within the 5′-flanking regions of the CYP2E1 gene [ 4 6 ]. Three genotypes of c1/c1, c1/c2, c2/c2 were generated; rs2031920 and rs3813867 were in close linkage disequilibrium [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, rs2031920 C/T with an Rsa I restriction enzyme site and rs3813867 C/T with a Pst I restriction enzyme site are two common single nucleotide polymorphisms (SNP) within the 5′-flanking regions of the CYP2E1 gene [ 4 6 ]. Three genotypes of c1/c1, c1/c2, c2/c2 were generated; rs2031920 and rs3813867 were in close linkage disequilibrium [ 4 6 ]. Furthermore, CYP2E1 polymorphisms were reported to be linked to several cancers, such as nasopharyngeal carcinoma [ 7 ], urinary cancers [ 6 ] and head and neck carcinoma [ 5 ], particularly in Asian populations.…”
Section: Introductionmentioning
confidence: 99%